Biomarker responses in zebrafish (Danio rerio) larvae exposed to pristine low-density polyethylene fragments. (April 2017) - Karami, Ali; Groman, David B.; Wilson, Scott P.; Ismail, Patimah; Neela, Vasantha K.
Abstract: There are serious concerns over the adverse impacts of microplastics (MPs) on living organisms. The main objective of this study was to test the effects of MPs on the total length, weight, condition factor (CF), transcriptional level of antioxidant, anti and pro-apoptotic, and neurotransmitter genes, and the histopathology of the gill, liver, brain, kidney, and intestine in the larvae of zebrafish ( Danio rerio ). Fish were exposed to one of three levels of pristine low-density polyethylene (LDPE) fragments (5, 50, or 500 μg/L) for 10 or 20 days. No significant changes were observed in any of the selected biomarkers across MP concentrations at days 10 or 20. The expression of casp9 (caspase 9, apoptosis-related cysteine protease), casp3a (caspase 3, apoptosis-related cysteine protease a) and cat (catalase), however, were significantly lower in the larvae sampled at day 20 than day 10. We provide evidence that virgin short-term exposure to LDPE fragments has minimal impact on biomarker responses in D. rerio larvae. Graphical abstract: Highlights: Zebrafish larvae were exposed to graded concentrations of LDPE for 10 or 20 days. Changes in the gene expressions and the histopathology of organs were investigated. None of the treatments significantly affected the biomarker responses. The expression of cat, casp 3a, and casp 9 were lower at the day 20 than day 10. Abstract : Exposure to LDPE fragments had limited effect on biomarker responses in D. rerio larvae.